2021
DOI: 10.3390/molecules26216569
|View full text |Cite
|
Sign up to set email alerts
|

A Novel N-Doped Nanoporous Bio-Graphene Synthesized from Pistacia lentiscus Gum and Its Nanocomposite with WO3 Nanoparticles: Visible-Light-Driven Photocatalytic Activity

Abstract: This paper reports the synthesis of a new nitrogen-doped porous bio-graphene (NPBG) with a specific biomorphic structure, using Pistacia lentiscus as a natural carbon source containing nitrogen that also acts as a bio-template. The obtained NPBG demonstrated the unique feature of doped nitrogen with a 3D nanoporous structure. Next, a WO3/N-doped porous bio-graphene nanocomposite (WO3/NPBG-NC) was synthesized, and the products were characterized using XPS, SEM, TEM, FT-IR, EDX, XRD, and Raman analyses. The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The O-O bond is dissociated and different oxygenated radicals are produced in the presence of water. These radicals can proceed the degradation of TCL via oxidation reaction [16,17,40]. P and S dopants also have the same function as nitrogen.…”
Section: Catalytic Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The O-O bond is dissociated and different oxygenated radicals are produced in the presence of water. These radicals can proceed the degradation of TCL via oxidation reaction [16,17,40]. P and S dopants also have the same function as nitrogen.…”
Section: Catalytic Studymentioning
confidence: 99%
“…Catalytic, photocatalytic, and electrocatalytic processes, ion exchange, and oxidation are the chemical processes used for wastewater treatment [10][11][12][13]. Among these methods, advanced oxidation processes (AOPs) are the well-known and effective methods for removal of various organic pollutants such as dyes, antibiotics, pesticides, and, etc [14][15][16][17][18][19][20]. Metal oxide semiconductors are the largest group of these catalysts that can fully destroy organic pollutants based on catalytic, photocatalytic, or electrophotocatalytic processes according to the different oxidation mechanism [19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…24 Afsharpour et al prepared WO 3 /N-doped porous bio-graphene nanocomposites possessing enhanced photocatalytic properties. 25 Jiang et al combined WO 3 and N-GQDs for the detection of E. coli with high sensitivity. 26 The excellent electrical conductivity of nitrogen-doped graphene facilitates the transfer of semiconductor photogenerated carriers and enhances the photoelectric properties.…”
Section: Introductionmentioning
confidence: 99%
“…Yousaf et al synthesized nitrogen-doped graphene-modified WO 3 nanocomposites to achieve better degradation of 2,4-dichlorophenol and methyl orange . Afsharpour et al prepared WO 3 /N-doped porous bio-graphene nanocomposites possessing enhanced photocatalytic properties . Jiang et al combined WO 3 and N-GQDs for the detection of E. coli with high sensitivity .…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [ 39 ] designed a novel one-dimensional/two-dimensional (1D/2D) core-shell cobalt monoxide/nickel-cobalt layered double hydroxide (CoO/Nico-LDH) heterojunction, which can avoid agglomeration, promote the transfer of photogenerated carriers, and expand the light absorption range, effectively enhancing the photocatalytic performance. As a conventional photocatalytic material, WO 3 has a band gap of about 2.5–2.8 eV [ 40 ], can absorb visible light at nearly 500 nm, and has good photocatalytic performance in visible light [ 41 , 42 , 43 ]. Cao et al [ 44 ] reported the electron transfer mechanism of noble-metal-free WO 3 @ZnIn 2 S 4 S-scheme heterojunction photocatalysts.…”
Section: Introductionmentioning
confidence: 99%